Burnout and Oncology: an irreparable paradigm or a manageable condition? Prevention strategies to reduce Burnout in Oncology Health Care Professionals. - Bui, Simona; Pelosi, Annalisa; Mazzaschi, Giulia; Tommasi, Chiara; Rapacchi, Elena; Camisa, Roberta; Binovi, Cinzia; Leonardi, Francesco (Acta Biomedica Atenei Parmensis, 2021)
Background: Burnout is a stress-induced occupational related syndrome, characterized by Emotional Exhaustion (EE), feeling of depersonalization (DP) and low sense of professional accomplishment (PA). The aim of this study is to analyse the effectiveness of interventions in decreasing health professionals Burnout as well as work and life-style risk factors. Methods: A survey in Medical Oncology Department in the University Hospital of Parma was conducted using the validated Maslach Burnout Inventory (MBI) and two additional questionnaires exploring lifestyle and work factors. An 8-months intervention involved fortnight meetings by facilitators, incorporated elements of reflection, shared experiences and managing emotions. Six months after the end of the intervention a second survey was performed among the participants using MBI and the same questionnaires mentioned above. Results: EE resulted the most problematic score in Day Hospital: after the 8-month intervention we described a significant decreasing in EE score especially for Day Hospital operators (from 16.7 to 10.9) and a considerable reduction in DP score. In the Oncology Ward a correlation between lack of collaboration among different health categories and DE score was detected; in the Day Hospital the absence of solid working teams was related to higher EE scores. Conclusion: The Oncology professional health care personnel are at the greatest risk of Burnout. Our study in Oncology Department shows that specific intervention should be used to prevent and reduce Burnout. Effective personal health care strategies should be incorporated into routine oncology care to prevent and treat Burnout.